Development of Thematic Digital Comics for Healthy Children During the Covid-19 Pandemic for PJOK Learning Class V Elementary School Students in Palembang - Bangkit Seandi Taroreh; Desy Arisandy (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The research aims to: 1) develop thematic digital comics for healthy children during the Covid-19 pandemic for learning PJOK for Class V Elementary School students in Palembang, 2) to determine the effectiveness of product implementation. The research method uses quantitative research with the ADDIE development model approach. The research subjects consisted of 1 physical education learning technology expert, 1 learning psychology expert, 3 PJOK teachers and 30 elementary school fifth grade students. Quantitative data were collected through questionnaire instruments and observation guidelines. Data analysis used descriptive quantitative. The results of the research are 1) it has produced a thematic digital comic model for healthy children during the Covid-19 pandemic for Grade V Elementary School Students in Palembang, 2) the percentage of effectiveness is 87.73% so it is very feasible to use. The hope is that it will become an alternative choice of learning media for physical education, sports and health (PJOK)